The gamma two-step cascade method at Dalat Nuclear Research Reactor - Vuong , Huu Tan; Pham , Dinh Khang; Tran , Tuan Anh; Nguyen , Nhi Dien; Nguyen , Xuan Hai; Ho , Huu Thang; Pham , Ngoc Son; Mangengo , Lumengano (Nuclear Science and Technology, 2014)
The event-event coincidence spectroscopy system was successfully established and operated on thermal neutron beam of channel N0. 3 at Dalat Nuclear Research Reactor (DNRR) with resolving time value of about 10 ns. The studies on level density, gamma strength function and decay scheme of intermediate-mass and heavy nuclei have been performed on this system. The achieved results are opening a new research of nuclear structure based on (n, 2ɣ) reaction.